Propulsive joint powers track with sensor-derived angular velocity: A potential tool for lab-less gait retraining - Hafer, J. F.; Zernicke, R. F. (Journal of Biomechanics, 2020)
Lower propulsive joint powers, particularly at the ankle, are often observed in older compared to young adults. Interventions to increase joint powers often require labs with motion capture and force treadmill technology. Translating these interventions out of the lab requires identifying portable measures that track (i.e., strongly correlate with) changes in joint powers. The purpose of this study was to determine if kinematics collected using inertial measurement units (IMUs) correlate with propulsive joint powers calculated using inverse dynamics. We collected data simultaneously with motion capture, force plates, and IMU sensors as young and older adults walked at varying speeds overground in a laboratory. Hip, knee, and ankle joint powers were calculated using inverse dynamics and positive peaks in the second half of stance were identified as the propulsive powers of interest. Raw IMU gyroscope data were oriented to a functional medial-lateral axis and peaks in the second half of stance were identified for segment (thigh, shank, foot) and joint (hip, knee, ankle) angular velocities. Pearson correlation coefficients were calculated between peak joint powers and peak angular velocities. We identified significant (all p < 0.001) correlations between hip joint power and hip and thigh angular velocities (r = 0.80-0.83) and between ankle joint power and ankle, shank, and foot angular velocities (r = 0.77-0.89). Correlation strength was similar between young and older adults and between segment and joint angular velocities. These results suggest that changes in joint powers longitudinally or over the course of an intervention could be tracked using a minimal set of wearable sensors.